OP23 Effects of living near an urban motorway on the wellbeing of local residents in deprived areas: natural experimental study. (13th September 2016) - Foley, L; Prins, R; Crawford, F; Humphreys, D; Mitchell, R; Sahlqvist, S; Thomson, H; Ogilvie, D
Abstract : Background: Individual and population wellbeing is partly shaped by neighbourhood physical environments, which have the potential to amplify social deprivation. In 2011, a five-mile extension to the M74 motorway was opened through predominantly urban, deprived areas of Glasgow. Proponents argued that the new motorway would improve mobility and contribute to wider regeneration and economic revival, which might improve wellbeing. Opponents countered that it would worsen wellbeing in local residents by increasing traffic noise, air pollution and severance (separation from amenities or social networks). We aimed to evaluate the effects of living near an urban motorway on wellbeing in local residents. Methods: We conducted a natural experimental study, using data from a longitudinal cohort nested within two distinct cross-sectional samples of adults aged 16 years or over who responded to postal surveys at baseline (2005) or follow-up (2013). We sampled from three matched study areas: the first surrounding the new M74 motorway extension; the second surrounding the established M8 motorway, constructed in the 1960s; and a third control area with no motorway. Within each area, individual exposure (proximity) to the nearest motorway was represented by the negative natural logarithm of the straight-line distance from each participant's home. Wellbeing was assessed using the mental (MCS-8) and physical (PCS-8) component summaries of the SF-8 scale at both time points, and the short Warwick-Edinburgh Mental Well-being Scale (SWEMWBS) at follow-up only. Linear regression analyses were conducted in Stata13 to explore associations between motorway exposure and wellbeing, adjusted for potential confounders. Results: 365 participants formed the cohort. The remaining 980 (baseline) and 978 (follow-up) participants together formed the repeat cross-sectional sample. Cohort participants living nearer to the new M74 motorway experienced significantly reduced mental wellbeing over time (MCS-8: −3.6, 95% CI −6.6 to −0.7) compared to those living further away. In cross-sectional and repeat cross-sectional analyses, an interaction was found whereby participants with a chronic condition living nearer to the established M8 motorway experienced reduced (MCS-8: −3.7, 95% CI −8.3 to 0.9) or poorer (SWEMWBS: −1.1, 95% CI −2.0 to −0.3) mental wellbeing compared to those living further away. Conclusion: Using a repeat cross-sectional analysis to complement and corroborate a cohort analysis subject to inevitable attrition over time, we found some evidence that living near to a new motorway worsened local residents' wellbeing. In an area with an existing motorway, negative impacts were concentrated in those with chronic conditions, which may exacerbate existing health inequalities.